Tri-Disciplinary Capacity Building: A Case Study of a Greater Bay Area Exchange Program and Its Impact on Lecturers' Competencies for SDGs-Aligned PKM - Dian Sudiantini; Desayu Eka Surya; Dyah Agustin Widhi Yanti; Rina Maria Hendriyani; Saili Rahmah (CV. Era Digital Nusantara, 2026)
Designing community service programs (PKM) aligned with the Sustainable Development Goals (SDGs) requires lecturers to possess integrated competencies in management, communication, and accounting. This study evaluates the impact of a one-week intensive exchange program to the Greater Bay Area (Hong Kong, Macau, Zhuhai, Shenzhen) in January 2026 on building these tri-disciplinary capacities. Using a participatory qualitative case study design, data was triangulated through pre- and post-program focus group discussions, content analysis of participant-developed PKM action plans, and observation of budgeting simulations. Findings indicate significant, interconnected growth across three core competency clusters: (1) Managerial Competence (evidenced by improved strategic planning for international projects), (2) Cross-Cultural Communication Competence (showcased through heightened sensitivity in navigating professional cultural differences), and (3) Financial-Accounting Literacy (demonstrated by a stronger grasp of transparency and sustainability in fund management). The synergy of these enhanced skills enabled lecturers to design more realistic, fundable, and impactful PKM proposals directly linked to specific SDGs, particularly Quality Education (4), Decent Work (8), Industry and Innovation (9), Sustainable Cities (11), and Partnerships (17). The study concludes that targeted short-term international exchanges are a potent catalyst for developing the holistic competency framework necessary to translate global agendas into viable, operational, and sustainable community engagement initiatives. This model offers a replicable strategy for lecturer professional development in an era of globalizing higher education.